Pengaruh Father Involvement Terhadap Self-Confidence Pada Siswa Sekolah Menengah Pertama (SMP) - Hasmi Amalia; Muhammad Arsyad; Ali Rachman (JURNAL BIMBINGAN DAN KONSELING AR-RAHMAN, 2026)
This study was motivated by the low level of self-confidence among junior high school students, characterized by a lack of courage in expressing opinions, withdrawal from social environments, and low confidence in personal abilities. This study aimed to analyze self-confidence and father involvement and to examine the effect of father involvement on self-confidence among students at SMP Negeri 8 Banjarmasin. A quantitative correlational design was employed, involving 267 students selected through a simple random sampling technique. Data were collected via questionnaires that had been tested for validity and reliability, and subsequently analyzed using descriptive statistics and simple linear regression with SPSS version 31. The analysis revealed that the majority of students displayed a moderate level of self-confidence (78.3%) and a moderate level of father involvement (72.7%). The results of the regression test indicated that father involvement significantly influenced students’ self-confidence, with a p-value of 0.002 and a contribution of 3.7% (R Square = 0.037). The positive association suggested that higher levels of father involvement were linked to greater student self-confidence. Therefore, while father involvement plays a role in developing students’ self-confidence, its overall impact remains relatively modest. _____________________________________________________________Penelitian ini berangkat dari permasalahan rendahnya tingkat kepercayaan diri siswa SMP yang ditandai dengan kurang berani mengemukakan pendapat, menarik diri dari lingkungan sosial, dan kurang yakin terhadap kemampuan diri. Penelitian ini berupaya guna menelaah self-confidence serta father involvement serta menguji dampak father involvement atas self-confidence pada siswa SMP Negeri 8 Banjarmasin. Penelitian mempergunakan pendekatan kuantitatif dengan jenis korelasional pengaruh. Sampel penelitian berjumlah 267 siswa yang dipilih mempergunakan teknik simple random sampling. Pengumpulan data dilaksanakan mempergunakan angket yang telah diuji validitas serta reliabilitasnya, kemudian dianalisis mempergunakan analisis deskriptif kuantitatif serta regresi linear sederhana dengan bantuan SPSS versi 31. Temuan mengindikasikan mayoritas siswa mempunyai tingkat self-confidence kategori sedang tercatat 78,3% serta father involvement kategori sedang 72,7%. Temuan uji regresi linear sederhana mengindikasikan father involvement berdampak signifikan atas self-confidence dengan nilai signifikansi 0,002 < 0,05 serta kontribusi 3,7% (R Square = 0,037). Arah korelasi positif mengindikasikan semakin tinggi father involvement maka semakin tinggi pula self-confidence siswa. Dengan demikian, keterlibatan ayah berperan dalam perkembangan kepercayaan diri siswa meskipun pengaruhnya relatif rendah.